Analysis of Salt Production, Consumption and Import in Indonesia - Ziecky Mardoni (International Journal of Science and Society, 2022)
This study aims to analyze and determine the effect of (1) consumption, capital, and labor on salt production in Indonesia (2) production, salt prices, imports, and Gross Domestic Product on salt consumption in Indonesia (3) consumption, exchange rates, and Gross Domestic Product on imports salt in Indonesia. This type of research is descriptive and associative. While this type of data is documentary data, the source of information is secondary data and data in the form of time series from 1986 - 2018. Simultaneous equation model analysis tools with the Two Stages Least Squared (TSLS) method. This study concludes that consumption of salt, capital, and labor has a significant influence on salt production in Indonesia. Salt production, salt prices, salt imports, and Gross Domestic Product significantly influence salt intake. Salt consumption and Gross Domestic Product have a significant effect on salt imports in Indonesia. Based on these results, the policy suggested is that the Government, through the Ministry of Agriculture, must issue a policy to encourage capital increase for salt production activities. In addition, the Government is also expected to increase the quantity and quality of workers who work in the industry so that the production of salt itself can be improved.